Investigação do monitoramento metacognitivo de crianças diante de medidas de capacidades intelectuais - Zampieri, Marília (2012)
Metacognition can be defined as the knowledge people have about their own cognitive processes, which can help them plan, monitor, regulate and assess their cognitive activities. Studies in the field have produced instruments and measures designed to assess metacognitive performance, many of them based on Flavell s Model of Cognitive Monitoring andas well as Nelsons and Narens model. The present study focused on gaining a better understanding of metacognitive monitoring, which is usually assessed through judgements, which represents one way of measuring metacognition. The aim of the present study was to investigate children s metacognitive monitoring during the execution of three subtests of the BMI (Multidimensional Battery of Child Intelligence), based on the Cattell-Horn-Carroll s model of intelligence. The subtests chosen assessed quantitative knowledge, crystallized intelligence and fluid intelligence. Participants were 44 fifht-year students, and each child was individually evaluated. Following each of the subtests, children were asked to estimate their performance. Results showed that children s repertoire included metacognitive abilities, and some metacognitive monitoring rates were better for quantitative knowledge . When these abilities were compared relative to cognitive performance, those with the highest scores on the intelligence subtests demonstrated better metacognitive monitoring. These results, obtained with Brazilian children, are compared with results reported in the international literature, and the implications in terms of promoting metacognitive training are discussed.